Collaboration between Guidance and Counseling Teachers and Indonesian Language Teachers to Improve Reading Motivation of Students through the CORI Program - Nurmasari, Yessika; Ramdhani, Rina Nurhudi (Jurnal Bimbingan dan Konseling Terapan, 2023)
One of the goals of guidance and counseling in elementary schools is to develop and improve students' academic abilities to achieve maximum learning abilities. Collaborative guidance to increase motivation to read is very rare in schools, especially in elementary schools where class teachers handle many subjects. Guidance services in elementary schools can be integrated into thematic learning activities. The research objective was to determine the effectiveness of collaborative guidance services between Guidance and Counseling teachers and Indonesian Language teachers to increase students' reading motivation. This research uses a quantitative approach with an experimental method with a quasi-experimental research design with the CORI (Concept-Oriented Reading Instruction) program. The results of the study showed that collaborative guidance between counseling teachers and Indonesian teachers was effective in increasing elementary school students' reading motivation. Research is suggested for elementary school guidance and counseling teachers to collaborate with subject teachers as an effort to optimize guidance and counseling services. Indonesian teachers can provide input for guidance and counseling services in the classroom. For future researchers, it can increase reading variety, reading exploration time and the application of collaborative guidance to increase reading motivation.